Analysis of land markets intended for single-family housing for different suburban areas - Przewięźlikowska, Anna (International Conference “Environmental Engineering”, 2017)
The aim of this article is the comparative description of two real estate markets based on the procedures for real property valuation. The study concerned only the land, which was undeveloped, intended for single-family housing in two communes located in the district of Krakow and three communes from the district of Kielce. The analyses were performed at four-year intervals and the comparison of the real estate markets was conducted. The first part contains the description of the areas covered by the research studies and the analyses of the real estate market and market trends. The next stage includes the descriptions of the two test real properties which are the subject of valuation and the fundamental comparative criterion. Then, the algorithms and methods of the calculations are presented. The practical part contains the description of individual markets, the implementation of the analyses and calculations, the comparison of the study areas and conclusions. The comparative analysis of the performed simulations of valuations was carried out first and then followed by a collective summary of descriptive statistics of all the real estate bases and the comparative description of the structures of the databases showing meaningful differences between Krakow and Kielce region.